Analyses of nonlinear dynamics of imperfect nanocomposite circular cylindrical shells with swirling annular and internal fluid flow using higher order shear deformation shell theory. (1st November 2019) - Ninh, Dinh Gia; Tien, Nguyen Duc; Hoang, Vu Ngoc Viet
Graphical abstract: Fig. 1a . Model of cylindrical shell with internal and external fluid flow. Highlights: Nonlinear dynamics of nanocomposite cylindrical shells with the internal and external fluid flow. The product of the velocity U.V of the two liquid streams (swirling flow and straight flow). The effect of the critical flow velocity, geometries and materials from periodic vibration to chaotic vibration of structure. Abstract: The paper focuses on nonlinear dynamical responses of circular cylindrical shell made of carbon nanotubes reinforced polymer conveying to internal and external fluid flow. The fluid flows are assumed incompressible. The governing equations are derived from the Third order shear deformation theory (TSDT), the fluid velocity potential, then using the Galerkin′s technique and the fourth-order Runge-Kutta method to give the characteristics of nonlinear dynamics of fluid-structures interaction. The product of the velocity U.V of the two liquid streams (swirling flow and straight flow) is considered to investigate the stable domain of the structure under the effect of two velocity factors. In addition, the dynamical behaviors as time histories and bifurcation diagram as well as the effects of materials, geometries and the critical velocities of losing stability caused by internal and external flow fluid are scrutinized in the present. The obtained results are also compared and validated with those of other studies and can be used as benchmark solutions for an analytical approach serving in further research.